Pengembangan Buku Cerita Berbasis Gurindam Dua Belas Sebagai Media Penanaman Sopan Santun di RA Alamsri Tanjunguban - Rofiati Rofiati; Hamid Patilima; Nita Priyanti (Jurnal Kajian Gender dan Anak, 2025)
The decline in positive character values among young children indicates a gap in the availability of engaging and culturally rooted learning media for character education. This study aims to develop a storybook based on Gurindam Dua Belas as an innovative medium to instill character values in early learners. The research employed a mixed-method approach with a Research and Development (RD) design following the 4D model (Define, Design, Development, Dissemination). The study involved 33 kindergarten level B students from three educational institutions in Tanjunguban, along with three teachers, one principal and four parents. Data were collected through structured interviews and observation sheets. Expert validation rated the product as “good” (media 80%, language 70%, material 80%). The storybook “Gurindam Cilik: Panca Indera Ajaibku” significantly improved children’s character scores, with the average increasing from 421.85 (pre-test) to 623.20 (post-test). A paired sample t-test confirmed the improvement as statistically significant (p = 0.037), representing a 47.7% increase. This study contributes an alternative learning medium that enables educators to instill positive character values from an early age through the integration of local cultural heritage enriched with moral lessons.